"Critical care without walls" - Impact of a "pediatric emergency team" on Picu admissions from the wards and overall mortality - Nitika Agrawal; Gnanam Ram; Shiv Kumar (Wolters Kluwer Medknow Publications, 2015)
A high index of suspicion is needed in pediatric patients with neurological symptoms being the sole presenting manifestation, to diagnose infection with the Human Immunodeficiency Vims (HIV). This is a write up of two such cases who were admitted to the pediatric intensive care unit with neurological manifestations. A 6 year old previously healthy child, who initially presented with intermittent drowsiness and fluctuation in blood pressure, later during hospital stay, developed progressive motor, cognitive, visual and language difficulties. Investigations revealed the child to be HIV positive and magnetic resonance imaging (MRI) findings were consistent with progressive multifocal leucoencephalopathy. A 12 yr old child had stroke initially (for which extensive work up had been done) and later, after 8 months presented with the same complaints along with severe pneumonia. He succumbed to severe opportunistic infections. That he was HIV positive, had not been detected during the first admission as left sided weakness was the only presenting manifestation.